Comparison of health-related fitness and modifiable lifestyle behaviors between SWAT officers and professional firefighters: An exploratory study - Joel Martin; Anne Akagi; Michael Toczko; Megan Sax van der Weyden; Joseph Hahn; Kayleigh Newman; Marcie Fyock-Martin (New Prairie Press, 2024)
Emergency responders engage in occupations that benefit from living a healthy lifestyle to ensure physical and mental preparedness. We compared fitness and healthy lifestyle behaviors between special weapons and tactics (SWAT) officers and firefighters. We analyzed data from 14 SWAT officers and 17 firefighters. Self-reported healthy lifestyle behavior measures included physical activity, sleep quality, and dietary behaviors. Fitness measures included body composition, flexibility, muscular strength, and endurance. Firefighters had higher (p < .05) body mass, body mass index, body fat percentage and fat mass than SWAT officers. SWAT officers performed better (p < .05) than the firefighters on vertical jump, push-ups, and a maximum plank hold. We found no difference regarding sleep quality or dietary behaviors; however, SWAT officers reported more minutes of vigorous (p = .006) and moderate-to-vigorous physical activity (p = .035). Our findings suggest that fitness and lifestyle behaviors vary among different emergency responder populations and public safety departments implementing health and wellness programs should consider the diversity of sub-groups of emergency responders that may exist within a department.